2014
DOI: 10.1063/1.4902821
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of polarization fluctuations to the nature of protein-water interactions: Study of biological water in four different protein-water systems

Abstract: Since the time of Kirkwood, observed deviations in magnitude of the dielectric constant of aqueous protein solution from that of neat water (∼80) and slower decay of polarization have been subjects of enormous interest, controversy, and debate. Most of the common proteins have large permanent dipole moments (often more than 100 D) that can influence structure and dynamics of even distant water molecules, thereby affecting collective polarization fluctuation of the solution, which in turn can significantly alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 65 publications
7
31
0
Order By: Relevance
“…From the THz to FIR region (0.25~12 THz), where we revealed the contribution of dissolved albumin solute is negligibly small, the hydration state and the water HB structure were analyzed. First, by defining hydration water as those water molecules that exhibit dynamically retarded reorientation compared with bulk water, we found z 3500 hydration water molecules corresponding to a layer of water molecules extending z 8.5 Å (three to four water layers) out from the protein surface, in good agreement with recent MD simulation studies (21,22). Second, the water HB structure around albumin is discussed in terms of HB fragmentation (the population of NHB water) and the distortion of the HB network.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…From the THz to FIR region (0.25~12 THz), where we revealed the contribution of dissolved albumin solute is negligibly small, the hydration state and the water HB structure were analyzed. First, by defining hydration water as those water molecules that exhibit dynamically retarded reorientation compared with bulk water, we found z 3500 hydration water molecules corresponding to a layer of water molecules extending z 8.5 Å (three to four water layers) out from the protein surface, in good agreement with recent MD simulation studies (21,22). Second, the water HB structure around albumin is discussed in terms of HB fragmentation (the population of NHB water) and the distortion of the HB network.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, by defining reorientationally retarded water as hydration water in our study, we found three to four water layers (~8.5 Å ) from the albumin surface exhibit water dynamics that distinguish it from that of bulk water. This ''global hydration'' view (21,22,(39)(40)(41)(42)(43)(44) is consistent with recent MD simulations, where the perturbation of water's orientational structure induced by the protein was found to be long-ranged, propagating out to three to five hydration shells (21,22).…”
Section: Hydration Statesupporting
confidence: 90%
See 3 more Smart Citations